2004
DOI: 10.1002/ijc.11721
|View full text |Cite
|
Sign up to set email alerts
|

WT1 is a tumor‐associated antigen in colon cancer that can be recognized by in vitro stimulated cytotoxic T cells

Abstract: The Wilms' tumor suppressor gene (WT1) has been shown to be overexpressed in acute and chronic leukemias and in a variety of solid human malignancies, including cancers of the breast and lung. In our present study, we investigated the potential role of WT1 gene in human colon cancer. WT1 mRNA and protein expression was analyzed in a panel of human colon cancer cell lines and primary colon carcinomas by RT-PCR and Western blot analysis, respectively. A mutational screen of WT1 zinc-finger region was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 48 publications
(53 reference statements)
1
47
0
Order By: Relevance
“…Our results, as well as those of other authors (15)(16)(17)(18)(19)(20), indicate that WT1 is important in cell proliferation in a large number of tumors. In addition, WT1 downregulation results in the inhibition of cell proliferation and apoptosis induction by caspase 3 expression and PARP cleavage, suggesting that WY1 plays a distinct role in B16F10 melanoma growth (5,37).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results, as well as those of other authors (15)(16)(17)(18)(19)(20), indicate that WT1 is important in cell proliferation in a large number of tumors. In addition, WT1 downregulation results in the inhibition of cell proliferation and apoptosis induction by caspase 3 expression and PARP cleavage, suggesting that WY1 plays a distinct role in B16F10 melanoma growth (5,37).…”
Section: Discussionsupporting
confidence: 90%
“…WT1 encodes a transcription factor with zinc finger motifs, which is involved in gonadal development, sexual differentiation, cell proliferation and apoptosis (12,13 is considered an oncogene rather than a tumor suppressor gene (14) because its high expression levels are associated with the development and progression of a number of neoplasias, such as leukemia, as well as solid tumors, including mesothelioma (15), breast (16), colon (17), ovarian (18) and lung (19) cancer, and melanoma (20). High WT1 mRNA expression levels have been correlated with a biologically aggressive phenotype that has been associated with a poor prognosis for leukemia (21) and sarcoma (22).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this upregulation is as yet unclear, as is the case for other tumors in the literature shown to contain elevated levels of WT1. 13,14 Our findings of WT1 overexpression in tumoral fibroblasts add to the growing spectrum of mainly epithelial tumors containing high levels of WT1. The exact role of WT1 in tumorigenesis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 69%
“…WT1 is expressed at high levels not only in most types of leukemia but also in various types of solid tumors, including lung and breast cancer. 13,14 Some reports suggested that deregulation of the Wnt signaling pathway plays a role in the genesis of some Wilms' tumors. One group reported ␤-catenin mutations in 21 of 153 (14%) Wilms' tumors 9 confirming an earlier observation showing ␤-catenin mutations in 6 of 40 (15%) Wilms' tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its recognized role in normal and aberrant haematopoiesis (62), WT1 was initially described as a tumour suppressor in Wilms' tumour (WT), a rare form of renal cancer (63-65), but can also play an oncogenic role in certain cancers (66)(67)(68)(69). Considering the recognized role of WT1 in WT of the kidney and in other cancers while also acting as a key transcriptional repressor/regulator of TPα expression in megakaryoblastic HEL and K562 cell lineages combined with the increasing awareness of the role of the TXA 2 -TP axis in neoplastic progression, we recently investigated the possible regulation of TPα/Prm1 by WT1 in prostate and breast cancer, including in the model prostate PC3 and breast MCF-7 [a model oestrogen receptor/oestrogen receptor (ER)-positive breast cancer cell line] and MDA-MB-231 (a model oestrogen receptor/ER, progesterone receptor/PR and Her2/neu triplenegative breast cancer cell line) carcinoma cell lines, respectively.…”
Section: Factors Determining Transcriptional Regulation Of Tpα In Plamentioning
confidence: 99%